Sexist language of “Pelakor and Pebinor” - Rezki Amalia Wahyuni Mustakim (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2019)
When in social media or everyday life rampant infidelity occurs, whether due to lifestyle, economy, and so forth. Economic demands intrigue principals to do so unnaturally. Until sometimes netizens make the acronym separate from the words of the affair, such as a beautiful interlude intact households, distractions in saturated times, a beautiful family interlude collapsed, and so forth. The perpetrators of infidelity sometimes even openly execute. Because they consider the affair is a natural thing in the present day. Infidelity sometimes happens either fiction or in a literary or non-fiction / real work. Society sometimes herded for various opinions that reflect one party. Be it both material and inmaterial matter. And this leads the author to issue words that lately often heard of the pelakor and pebinor.